Pengaruh Essensial Oil dari Biji Pala dan Lavender terhadap Tekanan Darah pada Lansia dengan Hipertensi - agung putri harsa satya nugraha; Eka Deviany Widyawaty (NERSMID : Jurnal Keperawatan dan Kebidanan, 2020)
Hypertension is still a health problem because it is the silent killer disease. Based on the results of Riskesdas in 2018, it was stated that the prevalence of hypertension was 34.1%. ¬Hypertension mostly occurred in the 55-64 years age group, namely 55.2%. The purpose of this study was to determine the effect of essential oil of nutmeg and lavender on the blood pressure of the elderly with hypertension in the working area of Arjowinangun Public Health Center, Kedungkandang District, Malang City. This research is a quantitative research with Quasi Experiment. The number of samples that met the inclusion criteria was 35 people. Quasi-Experimental Research carried out two observations, namely observation of blood pressure before and after being given nutmeg and lavender essential oils. The statistical test used was the Paired Sample T-Test with the results of the analysis of the p value = 0.000